Dionysos in Archaic Greece An Understanding through Images - Isler-Kerényi, Cornelia (Religions in the Graeco-Roman World, 2006)
An interpretation of the god Dionysos as seen by Greek vase painters before the golden age of classical culture, which will help understand his wide popularity beyond wine consumption, which lasted until the end of antiquity.